Bimbingan Akademik untuk Mereduksi Perilaku Menyontek Siswa Madrasah Tsanawiyah - Ajizah, Elis; Widiatmoko, Mualwi (Universitas Negeri Padang, 2017)
Academic guidance to reduce the cheating behavior of Madrasah Tsanawiyah students. This research is motivated by the cheating problem experienced by some of the students when facing test or repetition, if the behavior of cheating is left protracted, then the behavior will become a habit to form a dishonest person. The purpose of this study to obtain a general description of the behavior of students who cheat as a foundation in the preparation of academic guidance programs to reduce the cheating behavior of learners. This research uses a quantitative approach with descriptive research method with total population of 155 students in class VIII MTs. Rijalul Hikam Jatinagara academic year 2014/2015 using saturated samples. (2) The validation result according to BK that the academic guidance program service is feasible to be used to reduce cheating behavior. The recommendation of this research is an academic guidance program to reduce cheating behavior of learners can be used as an alternative of guidance and counseling services in overcoming the problems of learning, especially to reduce the cheating behavior of learners.